Inflammatory Cues Direct Skin-Resident Type 1 Innate Lymphoid Cells to Adopt a Psoriasis-Promoting Identity - Beatrix D.G. Evers; Miriam Hils; Christoph Heuser; Inga M. Hölge; Désirée Argiriu; Yuliya Skabytska; Susanne Kaesler; Christian Posch; Percy A. Knolle; Tilo Biedermann (Elsevier, 2023)
Innate lymphoid cells (ILCs) are gatekeepers in barrier organs, where they maintain tissue integrity and contribute to host defense as well as tissue repair. Inappropriate activation of ILCs, however, can lead to immunopathology with detrimental results. In this study, we focused on type 1 ILCs (ILC1s), which under inflammatory conditions constitute a poorly defined population with ambiguous functions. To delineate the properties of ILC1s in skin pathology, we used the well-established mouse model of imiquimod-induced psoriasis. Although ILC1s represented a minority among cutaneous lymphocytes in vehicle-treated controls, they rapidly expanded during early psoriasis and ultimately increased by >20-fold. This rapid increase was verified using two additional psoriasis models. Inflammatory ILC1s from imiquimod-treated skin were defined as CD44+, CXCR6+, and CD11b+ and substantially contributed to TNF-α and GM-CSF production, rendering them a potential candidate to shape the inflammatory infiltrate. In accordance with the psoriasis-specific microenvironment, skin ILC1s upregulated the IL-23 receptor whereas expression of the IL-12Rβ2 subunit was diminished. As a consequence, neutralization of IL-12 only had a minor impact, whereas blocking IL-23 reduced both ILC1 abundance and disease severity. Together, our findings identify skin ILC1s as a likely player in early psoriasis and a prospective target for therapeutic approaches.